Entity Structure and Taxes: An Analysis of Embedded Pass-Through Entities - Agarwal, Ashish; Chen, Shannon; Mills, Lillian F. (The Accounting Review, 2021)
ABSTRACT We examine the effect of pass-through entities embedded in corporate structures on tax avoidance, tax uncertainty, and tax noncompliance using unique, confidential tax return data that link corporations and pass-through entities together through Schedules K-1. We develop measures of the use of pass-through entities such as the number and “connectedness” of pass-throughs within the structure, the presence of loss pass-throughs or asymmetric allocations of such losses, and connections to entities external to the firm. We predict and find that these features are associated with lower effective tax rates, higher current-year additions to tax reserves, and larger amounts of proposed IRS audit adjustments, controlling for probability of audit selection. This large-sample evidence could help the IRS understand how pass-throughs affect compliance and financial statements users anticipate the tax effects related to entity structure. JEL Classifications: H20; H26; L22; M41.